CHEMICAL ASSESSMENT OF LIMESTONE DEPOSIT IN PARTS OF IJEBU MEMBER, DAHOMEY BASIN, NIGERIA - Richard, Fakolade Omotoso; Ayodele, Rotimi Isaac (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2020)
Fifteen rock samples were collected from some part of the Ijebu member of Ewekoro formation around Odogbolu, Southwestern Nigeria. These samples were analyzed for their elemental oxides and petrography to determine their depositional environment and rock provenance. The analysis was carried out using appropriate methods. The total organic carbon value ranges between 0.13% and 0.28% as against the threshold value of 0.30% for a good source of carbonate rock. The geochemical analysis indicates that the CaO percentage ranges from 19.12 to 52.69%, while the MgO percentage is generally low, ranging from 0.13 to 2.60%. This implies little or no dolomitization, and it indicates a good raw material for cement production. The SiO2 percentage ranges from 5.61 to 37.03%. These could have resulted from the slight incursion of the underlying Abeokuta formation, but studies revealed that it reduces as it grades towards the upper layers. The Fe2O3 percentages were relatively low. Further studies revealed that the limestones contain some fossils including foraminifera, gastropods, mollusks, echinoids and algae which have been recrystallized, obliterated and refilled by calcite during the diagenetic process.